DNA barcoding of the soft coral, Clavularia inflata, shows two major groups across Indonesian coral reefs - Beginer Subhan; Dietriech G. Bengen; Sebastian C. A. Ferse; Fauzan Dzulfannazhir; Luzmi Malia Izza; Nurlita Putri Anggraini; Prakas Santoso; Dondy Arafat; Lalu M. Iqbal Sani; Hawis H. Madduppa (Marine Science Department Diponegoro University, 2022)
Clavularia inflata was first described from Ternate Island, Indonesia in 1896 and later reported appeared from Japan and Taiwan in 1953.Clavularia (Blainville 1830) soft corals exhibit complex morphological traits that are difficult to differentiate, thus complicating their identification. DNA barcoding has been envisioned and actively pushed as a credible method for assigning unidentified specimens to known species by comparison to a molecular reference data database. Thus, the purpose of this study was to use molecular methods to confirm the identity of 25 colonies taken from 13 Indonesian coral reef sites and putatively identified as Clavularia inflata. All specimens were identified as Clavularia inflata molecularly using the mitochondrial DNA mtMuts gene. Although a comparison of the nucleotide base chains to Genbank data indicates that the samples belong to a single species, two clades in the phylogenetic tree and data from the Automatic Barcode Gap Discovery (ABGD) indicate that there are two major groups of C. inflata in Indonesia, implying cryptic species.